THE ROLE OF DIGITAL TECHNOLOGIES IN EMPOWERING PEOPLE WITH DISABILITIES IN INCLUSIVE EDUCATION (International Educators Conference, 2025)
In this article, the pedagogical foundations of fostering a healthy lifestyle among young people within the family are analyzed. The theoretical and methodological aspects of shaping a healthy lifestyle, the educational potential of the family, as well as the importance of parental responsibility are highlighted. Furthermore, the role of the family environment in strengthening the physical, spiritual, and psychological well-being of youth is emphasized, along with the educational significance of healthy nutrition, adherence to hygiene rules, and regular engagement in sports. The author also develops effective approaches to promoting a healthy lifestyle in the family based on contemporary pedagogical and psychological perspectives.